O Sistema judiciário brasileiro e o reconhecimento de identidades sociais - Silva, Rodrigo Umbelino da (Universidade Federal de São Carlos, 2011)
This present work is meant to examine the judiciary and the process of construction of social identities in Brazil after the 1988 Constitution. The search is assumed that after the process of democratization, the Brazilian state has experienced a new constitutionalism, encouraging new time to seek effective constitutional guarantees, setting up what will be called judicialization of politics in this inset the participation of the Judiciary, the Ministry public and civil society by the action of social movements, lead to a relentless pursuit of recognition and therefore construction of social identities. Understanding the relationship between law and politics, theoretical part of this arrangement, being guided by the phenomena of the contemporary debate legalization and judicial activism. The logic of any research that set the conceptual and empirical analysis of social transformations, guided by the action of those that structure the State, is the understanding that everything will be built will be based on a true democratic state of law, directing roughly the effective organization that society we want to search.
Keywords: Ciência política; Poder judiciário; Brasil - ministério público; Reconhecimento social; Identidade; Direito; Judicialização da política; Ativismo judicial; Movimento negro; The judiciary; Prosecution; Legalization of politics, Judicial activism; Recognition; Identity; Black movement; CIENCIAS HUMANAS::CIENCIA POLITICA